One-dimensional heat transfer in a convection-tip rectangular thin fin: a comparative study - Fakir, Md. Moslemuddin; Basri, Shahnor; Abu Bakar, Rosli; Rahman, Md Mustafizur (Faculty of Mechanical Engineering, Universiti Malaysia Pahang, 2010)
Among various numerical solution techniques, finite element method (FEM) and differential quadrature method (DQM) are two important of those. Usually elements are sub-divided uniformly in FEM (conventional FEM, CFEM) to obtain temperature distribution behavior in a fin. Hence, extra computational complexity is needed to obtain a fair solution with required accuracy. In this paper, non-uniform sub-elements are considered for FEM (efficient FEM, EFEM) solution to reduce the computational complexity. Then EFEM is applied for the solution of one-dimensional heat transfer problem in an convection-tip thin rectangular fin. The obtained results are compared with CFEM and efficient DQM (EDQM, with non-uniform mesh generation). It is found that the EFEM exhibits approximately 100% and 99% accuracy compared to CFEM and EDQM respectively showing its potentiality.